Inhibition by SR 140333 of NK1 tachykinin receptor-evoked, nitric oxide-dependent vasodilatation in the hamster cheek pouch microvasculature in vivo. - Hall, J M (1994)
1. This study investigated tachykinin-evoked vasodilatation in the microvasculature of the hamster cheek pouch in vivo. Arterioles and venules were observed by intravital microscopy with video recording, and vasodilatation and constriction, defined as changes in blood vessel diameter, measured by image analysis. All agents were applied topically by superfusion. None of the agents tested had a significant effect on venule diameter. 2. When arterioles were preconstricted (by ca. 50%) with endothelin-1 present in the superfusing medium, substance P (0.3-30 nM) was a potent vasodilator, being 10 fold more active than both neurokinin A and the NK1 receptor-selective agonist, substance P methyl ester. The NK2 receptor-selective agonist, [beta-Ala8]-NKA(4-10)(0.1-10 microM) was active only at high concentrations, and the NK3 receptor-selective agonist senktide (0.1-10 microM) was virtually inactive (n = 8 hamsters). Dilatation evoked by tachykinins and analogues was rapid in onset (< 0.5 min) and readily reversible. 3. At low concentrations (1-10 nM), the non-peptide tachykinin NK1 receptor antagonist SR140333 ((S)1-(2-[3(3,4-dichlorophenyl)-1-(3-iso-propoxyphenylacetyl)pi peridin-3- yl]ethyl)-4-phenyl-1-azoniabicyclo[2.2.2]octone, chloride) had no effect on the diameter of preconstricted arterioles per se, but potently inhibited dilator responses to substance P methyl ester (apparent pKB 9.9 +/- 0.2; n = 5 hamsters, n = 10 estimates). SR140333 (10 nM) did not inhibit submaximal dilator responses evoked by human alpha calcitonin gene-related peptide (alpha CGRPh; 1.0 nM; P > 0.05; n = 5).(ABSTRACT TRUNCATED AT 250 WORDS)